(3GdETGQGJ hGdJfHjgGJ aj GdefWb hGdMceIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3CeG HYO ajCjgG GdMQjU Ydi JMbjb GdMb ai gPg GdGTGQGJ hGdJfHjgGJ GUhdkG hLedkG ef GdMceI GdfgL GdChd ai ZQV GdefWb GdeQGO ef GdefWb s
(3BNQgG (B:s
(3GjgG GdGN Gfi eNUc ai gPg GdGTGQGJ aEf GPYJ gPG GdYde hGVYJg HGddg Hjfi hHjfc hcai HGddg hcjdG Je GdcJGH HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdadSaI hGdefWbs